Effect of Ultrasound‐Assisted Isolation on Yield and Properties of High‐Amylose Starch from Amylomaize. (23rd May 2019) - Liu, Jie; Wang, Yadan; Fang, Guihong; Man, Yong; Liu, Yawei
Abstract : Effect of ultrasound‐assisted wet‐milling on yield and properties of high amylose starch from amylomaize was investigated. The defibered mixture of starch and protein (mill starch) was sonicated by an ultrasonic processor. The highest yield of 56.68 % was obtained with steeping time of 36 h, ultrasonic power of 200 W, ultrasonic time of 15 min, and mill starch to water ratio of 1:1, while maintaining SO2 concentration of 0.05% in steepwater and a constant ultrasound frequency of 20 kHz. The starch isolated by sonication showed significantly lower b values (yellowness). Ultrasound did not cause changes in starch granular size, morphology, surface, and ordered structures at both short‐range and long‐range scale (p>0.05). The effect of ultrasound was also insignificant on thermal properties (p>0.05). The results demonstrated that the ultrasound did not alter the structures and properties of the isolated starches. Approximately 11% of starch yield was increased, 75% of SO2 content in steepwater was reduced and 25 % of steeping time was reduced by ultrasound‐assisted method compared with those of conventional wet‐milling process. Abstract : Effect of ultrasound‐assisted laboratory‐scale wet‐milling on yield and properties of high amylose starch from amylomaize is investigated in this study. Ultrasound did not cause changes in starch granular size, morphology, surface, ordered structures at both short‐range and long‐range scale and thermal properties. Approximately 11% of starch yield is increased, 75% of SO2 content in steepwater is reduced, and 25% of steeping time is reduced by ultrasound‐assisted method compared with those of conventional wet‐milling process, indicating an alternative promising starch production methods.